2018
DOI: 10.1007/s11892-018-1078-1
|View full text |Cite
|
Sign up to set email alerts
|

Biopsychosocial Factors Associated With Satisfaction and Sustained Use of Artificial Pancreas Technology and Its Components: a Call to the Technology Field

Abstract: Purpose of Review Summarize biopsychosocial factors associated with using continuous glucose monitors (CGMs), insulin pumps, and artificial pancreas (AP) systems and provide a “call to the field” about their importance to technology uptake and maintained use. Recent Findings Insulin pumps and CGMs are becoming standard of care for individuals with type 1 diabetes (T1D). AP systems combining a CGM, insulin pump, and automated dosing algorithm are available for commercial use. Despite improved glycemic control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 102 publications
1
27
0
Order By: Relevance
“…The youth in this real‐world study experienced nearly one Auto Mode exit per day, calibrated their sensor 2‐3 times per day, and checked blood glucose levels 5‐6 times per day. This is consistent with Faulds and colleagues' study, which reported that adults using 670G in the first 3 months calibrated their sensor 3.2 times/day and checked BG an average of 6.5 times/day . In an era when many individuals with type 1 diabetes are using factory calibrated CGM systems, requiring BG checks and sensor calibrations may be too high a burden for sustained use of HCL.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The youth in this real‐world study experienced nearly one Auto Mode exit per day, calibrated their sensor 2‐3 times per day, and checked blood glucose levels 5‐6 times per day. This is consistent with Faulds and colleagues' study, which reported that adults using 670G in the first 3 months calibrated their sensor 3.2 times/day and checked BG an average of 6.5 times/day . In an era when many individuals with type 1 diabetes are using factory calibrated CGM systems, requiring BG checks and sensor calibrations may be too high a burden for sustained use of HCL.…”
Section: Discussionsupporting
confidence: 88%
“…Youth may require substantial clinical support to overcome barriers in using CGM to ensure success in sustaining HCL use. Body image concerns, financial barriers, skin irritation, alarm fatigue, technical problems, and perceived lack of trust in the CGM glucose values are commonly cited barriers to CGM use in youth and young adults . It is important that health care providers and educators assess individual barriers to CGM use and provide psychosocial and educational support to assist youth in overcoming these barriers.…”
Section: Discussionmentioning
confidence: 99%
“…Other factors in addition to baseline HbA1c may also predict HCL discontinuation but were not detected in this current study. Diabetes distress, for example, has been shown previously to be associated with poorer T1D self‐management practices and glycemic control in youth with T1D, and should be further considered in light of the workload and alert fatigue described by HCL discontinuers. Other psychological factors may yield further insight into discontinuation of HCL, including self‐efficacy for diabetes care, or perceptions and expectations of HCL systems .…”
Section: Discussionmentioning
confidence: 99%
“…Participants then completed the quantitative portion, which consisted of 22 equally weighted possible burdens or problems with diabetes technology that the users and parents rated on a visual analog scale (VAS) developed by the study team. The scale included burdens described from the literature on device barriers with additional content added based on the study group's clinical experience and specific concerns with HCL. The survey prompt stated: “For the following questions, move the slider to indicate how much of a burden or problem the following have been for you when using the HCL device.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation